The Effect of Chlorine on The Reduction of Coliform and Total Suspended Solids in Domestic Wastewater at Port X Batam City in 2024 - Nur Jading, Rasmin; Herdianti, Herdianti; Saputra, Roni (Rifa'Institute, 2025)
Introduction: Daily activities at Port X generate domestic wastewater containing total coliform and Total Suspended Solids (TSS) levels exceeding the environmental quality standards. Elevated concentrations of these parameters pose a risk of waterbody pollution and can lead to gastrointestinal diseases in nearby communities. Objective: This study aims to evaluate the effect of calcium hypochlorite (kaporit) treatment on the reduction of total coliform and TSS in domestic wastewater at Port X, Batam City, in 2024. Method: A true experimental research method was employed, using a pretest-posttest control group design. Samples were treated with varying doses of calcium hypochlorite, followed by laboratory analysis to measure changes in coliform and TSS concentrations. Primary data were analyzed using paired t-tests with a significance level of p < 0.05. Result and Discussion: The results indicate that calcium hypochlorite treatment significantly reduces both total coliform counts and TSS levels. The most effective treatment was achieved with a dosage of 2 g/L of calcium hypochlorite combined with 4 hours of aeration, resulting in reduction efficiencies of 82.71% for total coliform and 85.16% for TSS. Conclusion: It can be concluded that calcium hypochlorite is effective in reducing pollutant loads in domestic wastewater, demonstrating its potential as an efficient and affordable solution for wastewater treatment in port areas.